1913 Okla. Sess. Laws 7, ch. 7, § 1. - (:unkn) unknown (General Publisher, 1913)
Any person who enters any building, railway car, vehicle, or structure and there opens or attempts to open any vault, safe, or receptacle used or kept for the secure keeping of money, securities, books of accounts, or other valuable property, papers or documents, without the consent of the owner, by the use of or aid of dynamite, nitroglycerine, gunpowder, or other explosives, or who enters any such building, railway car, vehicle or structure in which is kept any vault, safe or other receptacle for the safe keeping of money or other valuable property, papers, books, or documents, with intent and without the consent of the owner, to open or crack such vault, safe or receptacle by the aid or use of any explosive, shall in either case be deemed guilty of a felony,
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME